Graves, Crypts and Parthian Weapons excavated from the Gravesites of Vestemin - KARAMIAN, Gholamreza; FARROKH, Kaveh; KIAPI, Mohammad Fallah; LOJANDI, Hossein Nemati (Historia i Świat, 2018)
The article describes a series of finds of Parthian military items in the graves and crypts of Vestemin in northern Iran. These findings are especially significant as they provide an array of discoveries of military equipment: swords, daggers, spearheads, arrowheads, armor and a possible helmet. This study obliges a revision of Winkelman’s observation that “few finds of weapons have been made inside Iran” with respect to Parthian military equipment. In an overall sense, these findings may prove to be as significant to the domain of Parthian military studies as the well-known site of Dura Europos. The excavations have also discovered a coin of Philip the Arab or his son from the early Sasanian era which has assisted the authors’ dating of the Vestemin site. The site of Vestemin is not exclusively a burial venue as the site also has defense works as well as a fortress dated the later Parthian era c. 1st century BCE to 3rd century CE).